Social Interaction Of Hindus In The Middle Of Religious Plurality In Palangka Raya City - Ni Nyoman Rahmawati (IAHN-TP Palangka Raya, 2022)
The plurality of religions in Indonesia cannot be separated from the implementation of Presidential Decree No. 1. PNPS/1965 junto Law No. 5/1969 concerning the Prevention, Abuse and Blasphemy of Religion In the explanation article by article stating that there are six religions officially recognized by the State, namely religion Islam, Christianity, Catholicism, Hinduism, Buddhism, and Confucianism. This article aims to find out the social interaction of Hindus in the midst of religious plurality in Palangka Raya City. The study results indicate that the social interaction of Hindus in Palangkaraya City occurs in the institutional realm, between religious believers, and among Hindus themselves. Interaction in the institutional realm occurs in the form of the activeness of Hindus in various activities through institutions such as PHDI, WHDI, FKUB, PARADAH, and KMHDI. Inter-religious Hindus people interaction is manifested in the form of friendship, cooperation, and mutual support in times of grief. While the social interaction of Hindus among the people themselves occurs in the form of mutual cooperation (ngayah) at the time of piodalan, during the implementation of religious rituals such as Dewa Yadnya, Fitra Yadnya, Rsi Yadnya, Manusia Yadnya and Bhuta Yadnya.